PENGARUH GOOD CORPORATE GOVERNANCE PADA HUBUNGAN ANTARA SUSTAINABILITY REPORT DAN NILAI PERUSAHAAN (Studi Empiris Perusahaan Go Public di Indonesia Periode 2014-2015) - Ilham Nuryana Fatchan; Rina Trisnawati (Universitas Muhammadiyah Surakarta, 2016)
This study aims to investigate the influence of corporate governance and sustainability report on firm value of all companies listed in the Indonesia Stock Exchange. The data is secondary data which is obtained from the website www.ncsr-id.org, Indonesia Capital Market Directory (ICMD), and each website owned companies. The sample is companies that member of Indonesia Sustainability Report Award on the Indonesia Stock Exchange during 2014-2015. The sample was selected by purposive sampling method and obtained the 34 companies. Data analysis was performed with multiple regression method. The results show that sustainability report has a significantly influence on firm value, good corporate governance hasn’t a significantly influence on firm value and corporate governance as a moderating variable is not significantly influence on sustainability report and corporate value